Effect of Pressmud and Spentwash in Integration with Phosphogypsum on Yield and Economics of Wheat on Sodic Soils - Pagaria, P; Tetawat, K L (Annals of Arid Zone, 2016)
A field experiment was conducted during 2001-02 and 2002-03 at Research Station, Vallabhnagar (Udaipur, Rajasthan), to study the effect of pressmud (0.5, 10, 15 t ha,l) and spentwash (0, 2.5, 5.0, 7.5 lac L ha'l) with phosphogypsum (0, 25, 50% GR) on wheat productivity. Incorporation of phosphogypsum at 25% GR in integration with either pressmud or spentwash decreased the soil pH, EC and ESP and highest wheat grain yield was recorded with the treatment phosphogypsum at 25% GR. alone or with either pressmud (15 t ha'l) or spentwash (7.5 lac L ha,l). Incorporation of phosphogypsum beyond 25% GR had no significant effect on grain as well as straw yield of wheat. Incorporation of soil amendment increased the net returns and B:C ratio of wheat crop. The net returns and B:C ratio was under phospho gypsum at 50% and 25% GR, respectively, alone or with either spentwash at 7.5 lac L ha,l or press mud at 15 t ha,l. Key words: Spentwash, press mud, economics, wheat.